Dammarane-type saponins from steamed leaves of Panax Notoginseng - Liu, Qing (Springer Berlin Heidelberg, 2011)
Four new dammarane-type triterpenoid saponins, namely notoginsenosides SFt(1)-SFt(4) (1–4) were isolated from the steamed leaves of Panax notoginseng (Burk.) F. H. Chen (Araliaceae), together with 17 known saponins. Their structures were established on the basis of detailed spectroscopic analyses and acidic hydrolysis. The known ginsenosides Rk2 and Rh3 were obtained from P. notoginseng for the first time. All of these new saponins showed no in vitro cytotoxicity against five human cancer cell lines (HL-60, SMMC-7712, A-549, MCF-7, and SW480). [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/s13659-011-0036-2 and is accessible for authorized users.